Sebastian Fischer fischer at nii.ac.jp
Mon Sep 5 14:41:30 CEST 2011

```Hi again,

I think the following rules capture what Max's program does if applied after
the usual desugaring of do-notation:

a >>= \p -> return b
-->
(\p -> b) <\$> a

a >>= \p -> f <\$> b -- 'free p' and 'free b' disjoint
-->
((\p -> f) <\$> a) <*> b

a >>= \p -> f <\$> b -- 'free p' and 'free f' disjoint
-->
f <\$> (a >>= \p -> b)

a >>= \p -> b <*> c -- 'free p' and 'free c' disjoint
-->
(a >>= \p -> b) <*> c

a >>= \p -> b >>= \q -> c -- 'free p' and 'free b' disjoint
-->
liftA2 (,) a b >>= \(p,q) -> c

a >>= \p -> b >> c -- 'free p' and 'free b' disjoint
-->
(a << b) >>= \p -> c

The second and third rule overlap and should be applied in this order.
'free' gives all free variables of a pattern 'p' or an expression
'a','b','c', or 'f'.

If return, >>, and << are defined in Applicative, I think the rules also
achieve the minimal necessary class constraint for Thomas's examples that do
not involve aliasing of return.

Sebastian

On Mon, Sep 5, 2011 at 5:37 PM, Sebastian Fischer <fischer at nii.ac.jp> wrote:

> Hi Max,
>
> thanks for you proposal!
>
> Using the Applicative methods to optimise "do" desugaring is still
>> possible, it's just not that easy to have that weaken the generated
>> constraint from Monad to Applicative since only degenerate programs
>> like this one won't use a Monad method:
>>
>
> Is this still true, once Monad is a subclass of Applicative which defines
> return?
>
> I'd still somewhat prefer if return get's merged with the preceding
> statement so sometimes only a Functor constraint is generated but I think, I